Analyzing the Content of the Mathematics Curriculum for the Sixth Grade in the Light of the Behavioral Features of the Gifted Student in the Kingdom of Saudi Arabia - Al-Matt'hami, Mohammad Ahmad; Al-Matt'hami, Yahya Khader (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to identify the availability of behavioral features for gifted students that are required in the content of the mathematics curriculum for the sixth grade of elementary school at the Kingdom of Saudi Arabia. In order to achieve objectives of the study, the researcher used the descriptive and analytical approach which represented by the content analysis method; where the mathematics curriculum for the sixth grade of elementary school for both first and second semesters of the academic year 1443 AH was analyze. For this purpose, the researcher used the behavioral features model for gifted students (The Initial Nomination Model for Mawhiba Scale) as a tool for content analysis included (31) features distributed into five main domains as follow: mental flexibility, scientific and mechanical inference , linguistic inference and reading comprehension, mathematical and spatial inference and non-mental skills and abilities. The results of the study showed that the content of the mathematics curriculum for the sixth grade includes the following ratios: Mental flexibility with a percentage ranging between (22.72%- 13.17%) scientific and mechanical inference with a percentage ranging between (28.03%- 9.85%) , Linguistic inference and reading comprehension with a percentage ranging between (19.61%- 14.38%), mathematical and spatial inference with a percentage ranging between (22.61%- 17.18%), non-mental skills and abilities at a percentage ranging between (15.45%- 9.90%),the study found that behavioral features were less than average. The study found the availability of behavioral features at a lower than average rate. There are also some features that are very weak, which are access to general judgments based on previous information and results, oral expression in a distinct manner and the use of multiple ways to solve one problem. Accordingly, the researchers recommend the necessity of adopting these aspects in the curriculum to ensure its effectiveness.
Keywords: Mathematics Curriculum; Sixth Grade of Primary School; The Behavioral Features of the Gifted Student